Early Pleistocene hominin subsistence behaviors in South Africa: Evidence from the hominin-bearing deposit of Cooper's D (Bloubank Valley, South Africa). Issue 162 (January 2022) - Hanon, Raphaël; Patou-Mathis, Marylène; Péan, Stephane; Prat, Sandrine; Cohen, Brigette F.; Steininger, Christine
Abstract: Evidence of the consumption of meat through hunting or scavenging by Early Pleistocene hominins is scarce, particularly in South Africa. Moreover, the interpretations of taphonomic evidence are subject to an important discussion commonly called the 'hunting-vs-scavenging debate.' Until today, only the Swartkrans Members 1–3 site has yielded a butchered bone assemblage large enough to permit reconstruction of carcass acquisition strategies by Early Pleistocene hominins in South Africa. This leaves an information gap between 1.4 and 1.0 Ma. Here, we provide the first evidence of meat consumption by hominins during this gap, based on the zooarchaeological study of the large mammal bone assemblage recovered from the Cooper's D site, South Africa. Based on skeletal part representation, our results show density-mediated attrition of bovid bones due to predepositional and postdepositional destruction. We argue that this attrition is the result of both abiotic (i.e., decalcification) and biotic (i.e., carnivore ravaging) processes. Bovid mortality profiles point out the involvement of ambush predators such as large felids. Bone surface modifications also indicate that the assemblage has been accumulated mostly by carnivores but with some hominin involvement as well. We observe all the stages of animal carcass processing (skinning, disarticulation, defleshing, marrow extraction) as well as the exploitation of a diversity of prey size classes at both Swartkrans Members 1–3 and Cooper's D. Thus, our study shows the importance of the Cooper's D bone assemblage for understanding Early Pleistocene hominin subsistence behaviors. Moreover, this article highlights the need for including long bone flake specimens in the analysis of large bone assemblages from South African caves to better understand the Early Pleistocene hominin bone damage record.